Graphene–Curcumin Coatings Resistant to SARS-CoV-2 and Mycobacteria for the Production of Personal Protective Equipment. Issue 1 (31st December 2023) - De Maio, Flavio; Santarelli, Giulia; Palmieri, Valentina; Perini, Giordano; Salustri, Alessandro; Palucci, Ivana; Delli Carpini, Giovanni; Augello, Alberto; Sanguinetti, Maurizio; De Spirito, Marco; Sali, Michela; Delogu, Giovanni; et al.
ABSTRACT: Respiratory tract infections represent the main cause of death from infectious diseases worldwide. SARS-CoV-2 infection (i.e. COVID-19) added to the existing global burden of respiratory tract infections, including tuberculosis. Among nanomaterials for fabric functionalization, graphene, in combination with hydrophobic molecules such as phytochemicals, represents a promising low-cost alternative to antibiotics. In this work, we used graphene and curcumin to create fabric coatings on cotton and polyester for the production of personal protective equipment resistant to infective agents. These coatings ensure the trapping of microorganisms via interaction with SARS-CoV-2 or mycobacteria surface and inhibit microbial infections.